Maqashid Sharias Study on the Practice of Selling Gold that Has Not Been Paid off in Conditions of Urgent Need - Sy, Miftahul Zikri; Iska, Syukri (Rangkiang: Journal of Islamic Economics and Business, 2025)
This study aims to analyze the practice of buying and selling gold on credit from a sharia perspective, focusing on the principles of justice, transparency, and avoidance of elements of usury, gharar, and fraud. This phenomenon is becoming increasingly relevant as the public"s need for gold ownership as an investment instrument or value protection increases, even though they do not have the financial ability to buy in cash. The main problem studied in this study is when gold is still in installment status and has not fully become the property of buyers, especially in emergency conditions. The method used is descriptive qualitative research with a library research approach, which involves the analysis of classical and contemporary documents and literature related to fiqh muamalah, including the views of scholars from various schools and contemporary fatwas. The results of the study show that the practice of buying and selling gold on credit has room for ability in Islamic law, especially when gold is treated as a commodity (sil"ah) and not as a medium of exchange (tsaman). Despite differences of opinion among scholars regarding the legality of this transaction, the sharia maqashid approach provides legitimacy as long as the basic principles of sharia are maintained, such as justice, openness of contracts, and protection of weak parties. This research emphasizes the importance of a comprehensive understanding of contracts, payment mechanisms, and risks inherent in transactions so as not to deviate from sharia principles. Thus, the purchase and purchase of gold on credit can still be justified under sharia under certain conditions, as long as it meets strict conditions and signs in order to maintain benefits and avoid harmful practices